Improving nutritional quality and aflatoxin detoxification of peanut meal by co-fermentation with Weizmannia coagulans, Bacillus subtilis, and supplemented enzymes - Youwei Chen; Hao Huang; Dan Li; Limei Zou; Wendi Yu; Weiwei Dong; Xiang Yu; Yanli Feng; Jun Liu; Shumiao Zhao; Yunxiang Liang; Yuanliang Hu; et al. (Microbial Cell Factories)
Abstract Background Peanut meal, a high-protein agricultural by-product, faces challenges as animal feed due to anti-nutritional factors, poor protein digestibility, aflatoxin contamination, and imbalanced amino acids. Microbial fermentation is one of the most effective methods to reduce anti-nutritional factors and enhance the nutritional value of peanut meal. Compared to single-strain fermentation, microbial-enzyme co-fermentation exhibits enhanced degradation efficiency, accelerates nutrient release, improves product safety by reducing mycotoxins and anti-nutritional factors, enhances sensory properties, and increases fermentation consistency and stability. However, research on microbial-enzyme co-fermentation of peanut meal remains limited, particularly regarding the co-fermentation of Weizmannia coagulans and Bacillus subtilis with enzyme preparations, which has yet to be systematically investigated. Therefore, this study aims to evaluate and optimize the use of Weizmannia coagulans for microbial-enzyme co-fermentation to enhance the nutritional quality and reduce anti-nutritional factors in peanut meal. Results Peanut meal fermentation with Weizmannia coagulans BC01, Bacillus subtilis BS27, and the synergistic enzyme system (acid protease and hemicellulose) was optimized through single factor experiments and response surface methodology. This process led to significant reductions in crude fiber (from 7.05 to 2.88%) and anti-nutritional factors, with trypsin inhibitors decreasing from 0.30 to 0.03% and phytic acid from 1.43 to 0.35%. Aflatoxin B1 was reduced from 43.87 µg/kg to 6.20 µg/kg. Nutritional quality improved markedly, with flavonoid content increasing from 1.2 to 3.01%, reducing sugars increasing from 0.7 to 7.02%, and total acids increasing from 1.65 to 5.92%. Protein composition and digestibility were markedly improved, with crude protein, acid-soluble protein, and small peptide contents increasing by 18.2%, 546%, and 447%, respectively. Additionally, the degree of protein hydrolysis and in vitro digestibility rose to 40.77% and 68.91%, respectively. Total amino acid content increased by 14.3%, contributing to a more balanced amino acid profile. Conclusion The study indicates that microbial-enzyme co-fermentation involving W. coagulans effectively reduces anti-nutritional factors in peanut meal while enhancing its nutritional value. These findings provide a sustainable approach to transforming peanut meal into high-value animal feed, offering a practical solution to address the protein feed supply gap. Further validation via animal trials is necessary to evaluate its efficacy as a replacement for conventional protein feed sources.